Employee Service Performance in the Telecommunication Sector: The Role of Work Culture, Motivation, and Competence - Temi Delizar Hudoyo; Hapzi Ali (Dinasti International Journal of Management Science, 2026)
This study aims to analyze the influence of work culture, motivation, and employee competence on service performance in national telecommunication service companies. The research employs a Systematic Literature Review (SLR) approach using the PRISMA method to synthesize findings from 20 reputable journal articles (Scopus-indexed and SINTA 2 or above) published within the last five years (2020–2025). The findings indicate that work culture plays a crucial role in shaping employee behavior and service orientation, motivation significantly drives employee effort and service quality, and competence determines the effectiveness and consistency of service delivery. Simultaneously, these three variables exhibit a strong and significant influence on service performance. This study contributes by integrating organizational (culture), psychological (motivation), and individual capability (competence) factors into a unified framework for explaining service performance in the telecommunication sector.